Tapentadol Prolonged Release for Severe Chronic Osteoarthritis Pain in the Elderly—A Subgroup Analysis of Routine Clinical Practice Data. (14th April 2020) - Schwittay, Andreas; Sohns, Melanie; Heckes, Birgit; Elling, Christian
Abstract : Background . Tapentadol prolonged release (PR) has been shown effective and generally well tolerated in a broad range of chronic pain conditions. This subgroup analysis investigated its benefits for elderly patients with severe chronic osteoarthritis (OA) pain in routine clinical practice. Patients and Methods . Data of all patients with chronic OA pain were extracted from the database of a prospective, 3-month noninterventional tapentadol PR trial. The data of elderly OA patients (>65 years of age; n = 752) were compared with the data of younger OA patients (≤65 years; n = 282). Results . Almost all patients (elderly 98.7% and younger patients 99.3%) had received long-term analgesic medication prior to the start of tapentadol PR treatment but presented with severe pain accompanied by considerable impairments in sleep quality and quality of life measures. Tapentadol PR provided effective pain relief in both patient groups, with slightly better outcomes in younger patients. However, the mean baseline pain intensity of 7.1 (SD 1.5) was reduced by 3.8 points (p ≤ 0.001 ), and sleep and quality of life measures had also markedly improved in the elderly: quality of sleep by 3 points, quality of life by 3.4 points, social activities by 3 points, and independence by 2.7 points (p ≤ 0.001 for all measures; 11-point scale). At the end of observation, 68% of the elderly had clinically relevant pain reductions of at least 50% (vs baseline), and 87.9% attained either their intended pain reduction target and/or an additional individual treatment target (both predefined during baseline examination). Only 8.4% of the elderly experienced adverse drug reactions, most frequently nausea (2.7% of patients) and dizziness (1.5%). Conclusion . Tapentadol PR provided effective and well-tolerated treatment of severe chronic OA pain for elderly patients in routine clinical practice. The favorable tolerability profile in particular suggests tapentadol PR as a treatment option before classical strong opioids are considered.